Implementation of The Resident’s Dues Applications (SIUMAS) Using Waterfall Method in RT X Cinere Village - Febrianto, Febrianto; Aziz, Ikhwana Fakih Nur; Kosim, Mochammad Alvian; Darwis, Muhammad; Hendrowati, Retno (Universitas Trilogi, 2023)
Payment of dues is one of the obligations that must be fulfilled by every resident in a neighborhood association area. These dues are used for common purposes such as cleanliness and security. The collection and expenditure of dues are usually handled by the management committee. However, there are still difficulties in managing residents' dues using conventional methods. As a result, dues cards are often lost and the dues collection are not transparent. Therefore, the author developed The Resident’s Dues Application (SIUMAS) as a solution used to manage residents' dues. The purpose of developing this application is to simplify the management tasks of the committee in handling the collection and expenditure of dues, as well as to facilitate residents in tracking the utilization of the dues. This application is built using the PHP programming language and utilizes the MySQL database. The development of this application adopts an object-based application design method. The results of the SIUMAS application testing using Black Box Testing shown that all functionalities of the SIUMAS application are functioning well and meet the expectations.